Grace Nono music, inspiration and vision : a textual analysis - Manuel, Melvin Joseph R.
My study is a textual analysis of Grace Nono and her music employing the deconstruction approach. It focused on the factors, both internal and external, that may affect the works of an artist in one way or another. My work also focused on the politics of resistance reflected by Grace Nono herself and her music as well. A round of conversation with Grace Nono was conducted and her recordings were also analysed. This thesis revealed that generally, the work of an artist is influenced by how he feels about his environment or the society where he belongs. My study also found out that the personal life of an artist also poses a great impact on his work. Furthermore, this research also indicated that any woman could succeed in a patriarchal society like the Philippines. The details of this will be discussed intricately in the proceeding pages.